1994
DOI: 10.1111/j.1399-6576.1994.tb03981.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of five amino–amide local anaesthetic agents on human polymorphonuclear leukocytes measured by chemiluminescence

Abstract: The aim of this study was to assess the influence of five amino-amide local anesthetic agents on the production of oxygen metabolites in the human polymorphonuclear leukocyte (PMNL), both intra- and extracellularly. Ropivacaine, a new long-acting amino-amide local anaesthetic agent, bupivacaine, lidocaine, mepivacaine and prilocaine in concentrations 1-5 micrograms.ml-1 up to 500-1000 micrograms.ml-1 were compared to an untreated control. PMNLs were isolated from heparinized blood (healthy adult volunteers). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 33 publications
5
15
0
Order By: Relevance
“…Ropivacaine has also been found to exert protective effects in a rat colitis model (T. Martinsson, unpublished observation) and, as assessed using human neutrophils in vitro, to inhibit formation of reactive oxygen metabolites [18] as well as adhesion and expression of adhesion molecules [19]. These observations are in line with several previous studies indicating anti-inflammatory effects of local anesthetics other than ropivacaine [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 82%
“…Ropivacaine has also been found to exert protective effects in a rat colitis model (T. Martinsson, unpublished observation) and, as assessed using human neutrophils in vitro, to inhibit formation of reactive oxygen metabolites [18] as well as adhesion and expression of adhesion molecules [19]. These observations are in line with several previous studies indicating anti-inflammatory effects of local anesthetics other than ropivacaine [20][21][22][23][24][25][26].…”
Section: Introductionsupporting
confidence: 82%
“…Lidocaine has been shown previously to inhibit a variety of the stimulus-induced effector functions of leukocytes, including superoxide production, release of granule lysozyme and myeloperoxidase, and production of leukotriene B 4 and interleukin-1 [7,11,24,25]. In keeping with these findings, lidocaine significantly suppressed PMAinduced superoxide production in rabbit alveolar m. These actions of lidocaine are probably mediated through effects on cytoplasmic second messenger systems.…”
Section: Discussionsupporting
confidence: 75%
“…The findings of these in vivo studies are generally consistent with what is known of the effect of lidocaine on leukocytes in vitro. Lidocaine suppresses a number of leukocyte effector functions in vitro, including the respiratory burst, phagocytosis, inflammatory mediator release, and cell degranulation [7,8,11,[23][24][25]. The local anesthetic may also interfere with leukocyte housekeeping (homeostatic) functions, including intracellular pH (pH i ) regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine may also inhibit (via an unknown pathway) molecular interactions between immunoreactants and the surface of the leukocyte, leading to failed microtubular/microfilament changes and subsequent reduced superoxide anion production and failed occurrence of intracellular enzymes (11) at the inflammatory site. As a result, this can possibly decrease concentrations of known biologically active agents (4,15), including oxygen metabolites (16). In an earlier study, with topical lidocaine treatment in higher dosage, we found a decreased number of leukocytes in the inflammatory exudate during the first three days postoper-atively (13).…”
Section: -mentioning
confidence: 93%
“…Apart from studies using chemiluminescence (CL) (13,16), few details are known about the interactions of amide local anaesthetics with leukocyte oxygen metabolism in vivo. The major aim of the present study was therefore to investigate the effect of lidocaine on the production of H202, a relatively stable and potentially harmful metabolite of the leukocyte oxygen metabolism, at two different times in the surgical wound healing process.…”
Section: Introductionmentioning
confidence: 99%